پنڈت سندر لال کی کتاب”حضرت محمدؐ اور اسلام“ ایک تحقیقی جائزہ: A Research Analysis of Pandit Sundarlal’s book "Ḥazrat Muhammad (PBUH) Aur Islam" - Memoona Munir; Sahib Din; Professor Dr. Humayun Abbas (International Research Journal of Arabic and Islamic Studies, 2024)
The Holy Prophet (peace be upon him) is the radiant sun in terms of his character, whose reflection even non-Muslims could not remain without being affected by. Books have been written in the region. Many Hindu intellectuals have written works on the Prophet of Islam, including Shradhe Prakash Devji, Dr.Ved Prakash, Pandit Sundar Lal, Malik Ram, Dayanand Sir Soti, Swami Lakshman Parishad, Gobind Ram Setti Parishad Raghunath Sahay, etc. Included. In the article under discussion, Pandit Sundar Lal's book "Hazrat Muhammad PBUH and Islam" will be reviewed, which is a thick book on biography. In it, Pandit Sundar Lal has firstly mentioned the conditions of the Arabs and the treatment of women and slaves in Arabia and has presented the message of Islam and the good life of the Prophet (peace be upon him) with great beauty and devotion.